Ventral tegmental area inactivation suppresses the expression of CA1 long term potentiation in anesthetized rat. - Elham Ghanbarian (Public Library of Science (PLoS), 2013)
The hippocampus receives dopaminergic projections from the ventral tegmental area (VTA). Modulatory effect of dopamine on hippocampal long term potentiation (LTP) has been studied before, but there are conflicting results and some limitations in previous reports. Most of these studies show a significant effect of dopamine on the late phase of LTP in CA1 area of the hippocampus, while few reports show an effect on the early phase. Moreover, they generally manipulated dopamine receptors in the hippocampus and there are few studies investigating influence of the VTA neural activity on hippocampal LTP in the intact brain. Besides, VTA neurons contain other neurotransmitters such as glutamate and GABA that may modify the net effect of dopamine. In this study we examined the effect of VTA reversible inactivation on the induction and maintenance of early LTP in the CA1 area of anesthetized rats, and also on different phases of learning of a passive avoidance (PA) task. We found that inactivation of the VTA by lidocaine had no effect on CA1 LTP induction and paired-pulse facilitation, but its inactivation immediately after tetanic stimulation transiently suppressed the expression of LTP. Blockade of the VTA 20 min after tetanic stimulation had no effect on the magnitude of LTP. Moreover, VTA inactivation immediately after training impaired memory in the passive avoidance task, while its blockade before or 20 min after training produced no memory deficit. It can be concluded that VTA activity has no effect on CA1 LTP induction and acquisition of PA task, but involves in the expression of LTP and PA memory consolidation.